Cardiovascular disease (CVD) in Canadians with haemophilia: Age‐Related CVD in Haemophilia Epidemiological Research (ARCHER study). (29th July 2015) - Minuk, L.; Jackson, S.; Iorio, A.; Poon, M.‐C.; Dilworth, E.; Brose, K.; Card, R.; Rizwan, I.; Chin‐Yee, B.; Louzada, M.
<x xml:space="preserve">Abstract</x> Introduction Improvements in haemophilia care have increased life expectancy in persons with haemophilia (PWH). This ageing population presents clinicians with management challenges as they develop age‐related comorbidities such as cardiovascular disease (CVD). Aims To assess the epidemiology of CVD risk factors and events in an ageing Canadian haemophilia population. Methods A retrospective, multicentre chart review was carried out at five Canadian Hemophilia Treatment Centres. PWH (A and B) ≥35 years old were included and data were extracted on CVD risk factors and events. Results Data from 294 patients' charts were analysed including 222 (75.5%) patients with haemophilia A and 72 (24.5%) patients with haemophilia B with a median age at end of follow‐up of 54 years (range = 36–90). Mean follow‐up duration was 5.86 years. Cardiovascular risk factors were common: hypertension 31.3% (n = 90), diabetes mellitus 10.5% (n = 29), smoking 21.8% (n = 61), obesity 27.6% (n = 69), dyslipidaemia 22.4% (n = 65), family history 8.5% (n = 24), antiretroviral therapy 12.2% (n = 36). There were 24 CVD events (8.2% of the population) with a median age at event of 63 years (range = 46–83). Events consisted of coronary artery disease (CAD), 14; cerebrovascular disease, 4; and atrial fibrillation, 7. CAD was treated with coronary artery bypass grafting in three patients and percutaneous coronary intervention in nine patients. CVD events were complicated by six bleeding events (three minor and three major). Conclusion Cardiovascular disease risk factors and events are relatively common in PWH. PWH can be safely treated for CVD events with similar procedures as the non‐PWH populations, though specific clotting factor prophylaxis protocols are not well defined.